Foam sheet, product, molded article, and method for producing foam sheet

JP7639645B2Active Publication Date: 2025-03-05RICOH CO LTD
View PDF 29 Cites 0 Cited by

Patent Information

Application Number
JP2021165099
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-11-24
Filing Date
2021-10-06
Publication Date
2025-03-05
Estimated Expiration
2041-10-06

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、十分な生分解性を有しながら、耐熱性と高発泡倍率を両立した発泡シートを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639645000004
    Figure 0007639645000004
  • Figure 0007639645000005
    Figure 0007639645000005
  • Figure 0007639645000006
    Figure 0007639645000006
Patent Text Reader

Abstract

To provide a foamed sheet which, while having sufficient biodegradability, satisfies both of heat resistance and a high expansion ratio.SOLUTION: Provided is a foamed sheet formed of a composition comprising polylactic acid. The polylactic acid is such that either of D form or L form of lactic acid which constitutes the polylactic acid has a content of 98 mol% or more. The polylactic acid has a content of 98 mass% or more relative to a total amount of organic matter in the foamed sheet. A bulk density of the foamed sheet is 0.063 g / cm3 to 0.125 g / cm3.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a foam sheet, a product, a molded article, and a method for producing a foam sheet. [Background technology]

[0002] Plastics are processed into various product shapes such as bags and containers and are widely distributed. However, plastic products are difficult to decompose in nature, so disposal after use is a problem. In recent years, with the increase in environmental awareness, there has been active development of materials to replace non-biodegradable plastics, which are difficult to decompose in nature, with biodegradable plastics, which are easily decomposed in nature.

[0003] Among biodegradable plastics, polylactic acid has attracted attention as a possible alternative to non-degradable plastics because its properties are similar to those of polystyrene, which is a plastic traditionally used.

[0004] One of the uses of polystyrene is expanded polystyrene, which is made by expanding polystyrene to give it properties such as light weight, shock-absorbing properties, and heat insulation, and is widely used. Expanded polylactic acid, which uses polylactic acid, a biodegradable plastic, has also been proposed as an environmentally friendly alternative to such expanded polystyrene (see, for example, Patent Documents 1 to 4).

[0005] However, it is generally pointed out that polylactic acid has low heat resistance due to its low glass transition temperature (about 60°C). For example, when polylactic acid is used for food containers, the polylactic acid food containers can suffer from problems such as deformation and holes when exposed to boiling water or cooked in a microwave oven.

[0006] Methods proposed for improving the heat resistance of polylactic acid include blending with inorganic clay (Patent Document 5), stereocomplexes which are blends of optical isomers of polylactic acid (Patent Documents 6 to 8), introduction of chemical crosslinks (Patent Document 9), and a method of complexing with acrylic resin (Patent Document 10). In addition, a method of improving heat resistance by increasing the crystallinity of polylactic acid is also known as a publicly known technology.

[0007] However, in regard to Patent Documents 5, 9, and 10, considering that polylactic acid containers are composted, incinerated, recycled, etc. after use, it is desirable that the composition of the polylactic acid container is made of only a single biodegradable plastic or is manufactured from a composition as close as possible to only biodegradable plastic, and it is also desirable to introduce as little crosslinking as possible, since this reduces biodegradability. Therefore, these proposals were not satisfactory as a method for obtaining polylactic acid food containers with sufficient biodegradability and heat resistance.

[0008] Regarding Patent Documents 6 to 8, the method using a stereocomplex is such that the poly-(D)-lactic acid is currently very expensive and cannot be commercially provided as a disposable food container or the like. Summary of the Invention [Problem to be solved by the invention]

[0009] An object of the present invention is to provide a foamed sheet which has sufficient biodegradability while also achieving both heat resistance and a high expansion ratio. [Means for solving the problem]

[0010] In order to solve the above problems, the foamed sheet of the present invention comprises: A foamed sheet made of a composition containing polylactic acid, the polylactic acid containing 98 mol % or more of either the D-form or the L-form of lactic acid constituting the polylactic acid, the polylactic acid containing 98 mass % or more of the total amount of organic matter in the foamed sheet, and the bulk density of the foamed sheet is 0.065 g / cm 3 More than 0.085g / cm 3 Below The foam sheet contains an epoxy-based crosslinking agent, and the epoxy-based crosslinking agent accounts for 1.3% by mass or more and 1.7% by mass or less of an organic component amount in the foam sheet. It is characterized by: Effect of the Invention

[0011] According to the present invention, it is possible to provide a foamed sheet which has sufficient biodegradability while also achieving both heat resistance and a high expansion ratio. [Brief description of the drawings]

[0012] [Figure 1] 1 is a phase diagram showing the state of matter versus temperature and pressure. [Diagram 2] FIG. 1 is a phase diagram for defining a range of compressible fluids. [Diagram 3] FIG. 2 is a schematic diagram showing an example of a kneading device. [Figure 4] FIG. 2 is a schematic diagram showing an example of a foam sheet forming apparatus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The foamed sheet, the product, and the method for producing the foamed sheet according to the present invention will be described below with reference to the drawings. Note that the present invention is not limited to the following embodiments, and may be modified within the scope of what a person skilled in the art can imagine, such as other embodiments, additions, modifications, deletions, etc., and any embodiment is included in the scope of the present invention as long as it exhibits the functions and effects of the present invention.

[0014] The foamed sheet of the present invention is a foamed sheet made of a composition containing polylactic acid, wherein either the D-form or the L-form of lactic acid constituting the polylactic acid is 98 mol % or more in the polylactic acid, the polylactic acid accounts for 98 mass % or more of the total amount of organic matter in the foamed sheet, and the bulk density of the foamed sheet is 0.063 g / cm 3 More than 0.125g / cm 3 The present invention is characterized in that:

[0015] In the prior art, it is a well-known fact that the method of using highly crystalline polylactic acid is effective in obtaining molded products with excellent heat resistance, but as the crystallinity increases, the rigidity of the resin increases, and it was difficult to obtain a sheet with a high expansion ratio in the first place. When using a foamed sheet as a food container, it is desirable to have a high expansion ratio as long as the strength of the structure can be maintained from the standpoint of thermal insulation and resource conservation, and therefore, in order to use a polylactic acid foamed sheet as a heat-resistant food container, it was required to achieve both a high expansion ratio and heat resistance.

[0016] In contrast, the present invention can provide a foamed sheet that has sufficient biodegradability while also achieving both heat resistance and a high expansion ratio. Since the foamed sheet of the present invention is made of a composition containing polylactic acid, the foamed sheet of the present invention may be called a polylactic acid foamed sheet, a foamed polylactic acid composition sheet, or the like. As will be described in detail later, the foamed sheet of the present invention has good heat resistance and can be used, for example, as a heat-resistant food container. The foamed polylactic acid composition sheet refers to a sheet-like product made by foaming a composition containing polylactic acid.

[0017] (Foam sheet) The foamed sheet of the present invention is made of a composition containing polylactic acid. The composition contains polylactic acid and may contain other ingredients such as fillers, and refers to the state before foaming. Since the composition contains polylactic acid, it may be called a polylactic acid composition. The composition further contains other ingredients such as a crosslinking agent as necessary.

[0018] As a result of investigations conducted by the inventors to solve the above-mentioned problems, they discovered that the problems could be solved by adjusting high optical purity polylactic acid (also called polylactic acid-based resin or polylactic acid resin) to an appropriate viscosity in a temperature range where crystallization occurs slowly, and then forming uniform fine bubbles, which led to the completion of the present invention.

[0019] In the foamed sheet of the present invention, it is preferable to finely foam a polylactic acid resin having high optical purity to a high foaming ratio. Fine foaming effectively promotes elongation crystallization accompanying elongation deformation on the bubble surface, making it possible to obtain a sheet with excellent heat resistance. In addition, the miniaturization of the foam diameter reduces the thermal conductivity of the foamed sheet, making it possible to obtain a sheet with excellent heat resistance.

[0020] Generally, polylactic acid has a low viscosity near its melting point, and bubbles tend to coalesce and break, so that it is difficult to make the foam diameter fine and to increase the foaming ratio. Patent Documents 1 and 4 describe polylactic acid foam sheets, but the prior art did not satisfy these demands. In particular, the fine foam disclosed in Patent Document 4 uses carbon dioxide as a foaming agent to obtain a foam diameter of 1 μm or less, but it is produced by a batch device that foams under conditions below the melting point of the polymer, and it is not suitable for industrial mass production by a continuous process.

[0021] <Polylactic acid> Polylactic acid resin is biodegradable by microorganisms, and is therefore attracting attention as an environmentally friendly polymer material with a low environmental impact (see "Structure, Properties, and Biodegradability of Aliphatic Polyesters, Polymers, Vol. 50, No. 6, 2001, pp. 374-377").

[0022] Examples of the polylactic acid include copolymers of D-lactic acid and L-lactic acid, homopolymers of either D-lactic acid (D-form) or L-lactic acid (L-form), and ring-opening polymers of one or more lactides selected from the group consisting of D-lactide (D-form), L-lactide (L-form) and DL-lactide. These may be used alone or in combination of two or more. The polylactic acid may be appropriately synthesized or commercially available.

[0023] When a copolymer of D-lactic acid and L-lactic acid, or a ring-opening polymer of one or more lactides selected from the group consisting of D-lactide, L-lactide, and DL-lactide is used as the polylactic acid, the crystallinity tends to increase and the melting point and crystallization rate tend to increase as the amount of the lesser optical isomer of the D-form and L-form decreases, and the crystallinity tends to decrease and eventually become amorphous as the amount of the lesser optical isomer increases.

[0024] In the present invention, since it is necessary to provide sufficient heat resistance by crystallization accompanying bubble growth during foaming, either the D-form or the L-form of the lactic acid constituting the polylactic acid contained in the composition is 98 mol% or more in the polylactic acid. For this reason, polylactic acid consisting of only one of the optical isomers of the D-form or the L-form may be used. If the above is not satisfied, good heat resistance cannot be obtained. It is to be noted that the range may be greater than 98 mol% as necessary.

[0025] Whether the polylactic acid in the foamed sheet contains 98 mol % or more of either the D- or L-form of lactic acid constituting the polylactic acid can be confirmed by analyzing the polylactic acid by liquid chromatography using an optically active column. The measurement procedure is as follows. The foam sheet is freeze-pulverized, 200 mg of the foam sheet powder is placed in an Erlenmeyer flask, and 30 ml of 1N sodium hydroxide solution is added. Next, the Erlenmeyer flask is heated to 65°C while being shaken to completely dissolve the polylactic acid. Next, the pH is adjusted to 4-7 using 1N hydrochloric acid, and the solution is diluted to a specified volume using a measuring flask to obtain a polylactic acid solution. Next, the polylactic acid solution is filtered through a 0.45 μm membrane filter and then analyzed using a liquid chromatograph. Based on the obtained chart, the area ratio is calculated from the peaks derived from the D- and L-forms, and the amount of the D- and L-forms is calculated based on the abundance ratio. The arithmetic mean value of the results obtained by performing the above operation three times is taken as the amount of the D- and L-forms of lactic acid constituting the polylactic acid in the foamed sheet.

[0026] The measuring device and conditions are as follows. HPLC device (liquid chromatography): JASCO Corporation product name "PU-2085Plus system" Column: Sumitomo Analysis Center Co., Ltd. product name "SUMICHIRALOA5000" (4.6mmφ×250mm) Column temperature: 25℃ Mobile phase: A mixture of 2 mM CuSO4 aqueous solution and 2-propanol (CuSO4 aqueous solution:2-propanol (volume ratio) = 95:5) Mobile phase flow rate: 1.0 ml / min Detector: UV254nm Injection volume: 20 microliters

[0027] When the foamed sheet is subjected to the above measurement, if the area of ​​the larger peak of the D- and L-forms is 98% or more of the total area of ​​the peaks originating from the D- and L-forms, it can be said that either the D- or L-form of the lactic acid constituting the polylactic acid is 98 mol% or more in the polylactic acid. In addition, if the optical purity is 98% or more, it can be said that the polylactic acid satisfies the above requirements.

[0028] Here, the term "crystallinity" broadly refers to the degree of crystallization and the crystallization rate, and high crystallinity means high degree of crystallization and / or high crystallization rate.

[0029] The content of polylactic acid is 98% by mass or more based on the total amount of organic matter in the foamed sheet from the viewpoints of biodegradability and recyclability (facilitating recycling). If the content is 98% by mass or more, problems caused by other components remaining that are not biodegradable even if the polylactic acid is biodegraded can be prevented. If the content is less than 98% by mass, good biodegradability cannot be obtained.

[0030] The organic matter in the foamed sheet is mainly polylactic acid, and other than polylactic acid, for example, an organic core material (also called organic filler), a crosslinking agent, etc. When an inorganic core material (also called inorganic filler) is used as a filler, the inorganic core material does not fall under the category of the organic matter.

[0031] -Method for measuring polylactic acid content- The content of polylactic acid can be calculated from the ratio of the materials used. If the material ratio is unknown, for example, the following GCMS analysis can be performed and the components can be identified by comparing with a known polylactic acid standard sample. If necessary, it is also possible to calculate by combining the spectrum area ratio from NMR measurement and other analytical methods.

[0032] [Measurement by GCMS analysis] GCMS: Shimadzu QP2010, Frontier Lab Py3030D Separation column: Frontier Labs Ultra ALLOY UA5-30M-0.25F Sample heating temperature: 300℃ Column oven temperature: 50°C (1 minute hold) - Heat up 15°C / min - 320°C (6 minutes) Ionization method: Electron Ionization (EI) method Detection mass range: 25 to 700 (m / z)

[0033] The content of the organic filler can also be determined by the same GCMS analysis.

[0034] <<Total amount of organic matter, amount of inorganic filler>> The total amount of organic matter in the foamed sheet can be estimated as the amount excluding ash (= inorganic component amount). The ash amount can be considered as the amount of inorganic filler. The ash amount is the residue when burned at 600℃ for 4 hours. The ash content was measured as follows. Approximately 3 g of the foamed sheet sample was weighed into a 100 mL crucible whose weight had been accurately measured to four decimal places using a precision balance, and the total weight of the crucible and sample was accurately measured. The crucible was placed in a Yamato Scientific FP-310 muffle furnace and burned at 600°C for four hours to combust the organic components. The crucible was then cooled in a desiccator for one hour, and the crucible was weighed again to measure the total weight of the crucible and ash content. The ash content, i.e., the amount of inorganic filler and the total amount of organic matter, are calculated by the following formula.

[0035] Amount of inorganic filler [%] = Amount of ash [%] = (Total weight of crucible and sample after combustion and cooling [g] - Weight of crucible [g]) / (Total weight of crucible and sample before combustion [g] - Weight of crucible [g]) × 100

[0036] Total organic matter [%] = 100 - ash content [%]

[0037] The above measurement was carried out twice (n=2), and the average value was calculated.

[0038] <Filler> The filler (hereinafter sometimes referred to as "foam nucleating material" or "foam nucleating agent") is contained to adjust the cell diameter and number density of the foamed sheet and to improve crystallinity.

[0039] The filler may be an inorganic core material, an organic core material, etc. These may be used alone or in combination of two or more kinds.

[0040] Examples of the inorganic core material include talc, kaolin, calcium carbonate, layered silicate, zinc carbonate, wollastonite, silica, alumina, magnesium oxide, titanium oxide, calcium silicate, sodium aluminate, calcium aluminate, sodium aluminosilicate, magnesium silicate, glass balloons, carbon black, zinc oxide, antimony trioxide, zeolite, hydrotalcite, metal fibers, metal whiskers, ceramic whiskers, potassium titanate, boron nitride, graphite, glass fibers, and carbon fibers.

[0041] Examples of the organic core material include naturally occurring polymers such as starch, cellulose nanofibers, cellulose fine particles, wood flour, soybean pulp, rice husks, and bran, as well as modified products thereof, glycerin compounds, sorbitol compounds, metal salts of benzoic acid and its compounds, metal salts of phosphate esters, and rosin compounds.

[0042] Among these, silica, titanium oxide, and layered silicates are more preferable as inorganic core materials because they can be efficiently dispersed, the amount added can be reduced, and the environmental load can be reduced.

[0043] From the viewpoint of increasing the surface area per added amount and reducing the amount added, the filler preferably has a number average length in the minor axis direction of 100 nm or less.

[0044] The content of the filler in the foamed sheet is preferably 3% by mass or less. If it exceeds 3% by mass, the physical properties of the foamed polylactic acid composition sheet may become hard and brittle. The content of the non-biodegradable filler is preferably as small as possible, and more preferably 1% by mass or less in the foamed sheet.

[0045] <Other ingredients> The other components are not particularly limited so long as they are normally contained in a foamed sheet and may be appropriately selected depending on the purpose. For example, a crosslinking agent may be mentioned.

[0046] <<Crosslinking agent>> The crosslinking agent is not particularly limited as long as it is a compound reactive with the hydroxyl group and / or carboxylic acid group of polylactic acid. For example, an epoxy-based crosslinking agent (a crosslinking agent having an epoxy group) or an isocyanate-based crosslinking agent (a crosslinking agent having an isocyanate group) is preferably used. As these crosslinking agents, for example, an epoxy-functional (meth)acrylic-styrene-based crosslinking agent having two or more epoxy groups in the molecule, or a polyisocyanate having two or more isocyanate groups in the molecule is preferred. From the viewpoint of efficiently improving the melt strength by introducing a branched structure into polylactic acid and reducing the amount of unreacted material remaining, an epoxy-functional (meth)acrylic-styrene-based crosslinking agent having three or more epoxy groups in the molecule, or a polyisocyanate having three or more isocyanate groups in the molecule is more preferred. By using such a crosslinking agent, it is possible to suppress the coalescence and breakage of bubbles, and to improve the expansion ratio.

[0047] Here, the epoxy-functional (meth)acrylic-styrene-based crosslinking agent having two or more epoxy groups in the molecule is a polymer obtained by copolymerizing a (meth)acrylic monomer having an epoxy group with a styrene monomer.

[0048] Examples of (meth)acrylic monomers having an epoxy group include monomers containing a 1,2-epoxy group such as glycidyl acrylate, glycidyl methacrylate, etc. Examples of styrene monomers include styrene, α-methylstyrene, etc.

[0049] An epoxy-functional (meth)acrylic-styrene crosslinking agent having two or more epoxy groups in the molecule may contain a (meth)acrylic monomer having no epoxy group in its copolymerization component. Examples of such (meth)acrylic monomers include methyl acrylate, ethyl acrylate, propyl acrylate, butyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, butyl methacrylate, and cyclohexyl methacrylate.

[0050] Examples of polyisocyanates having two or more isocyanate groups in the molecule include 1,6-hexamethylene diisocyanate, 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (isophorone diisocyanate), 1,4-tetramethylene diisocyanate, 2,4,4-trimethylhexamethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, dicyclohexylmethane-4,4'-diisocyanate, methylcyclohexyl-2,4-diisocyanate, methylcyclohexyl-2, Aliphatic diisocyanates such as 6-diisocyanate, xylylene diisocyanate, 1,3-bis(isocyanate)methylcyclohexane, tetramethylxylylene diisocyanate, transcyclohexane-1,4-diisocyanate, and lysine diisocyanate; alicyclic polyisocyanates such as isophorone diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylylene diisocyanate, hydrogenated tetramethylxylylene diisocyanate, and cyclohexane diisocyanate; 2,4-toluylene diisocyanate Aromatic diisocyanates such as anate, 2,6-toluylene diisocyanate, diphenylmethane-4,4'-isocyanate, 1,5'-naphthene diisocyanate, tolidine diisocyanate, diphenylmethylmethane diisocyanate, tetraalkyldiphenylmethane diisocyanate, 4,4'-dibenzyl diisocyanate, 1,3-phenylene diisocyanate, lysine ester triisocyanate, triphenylmethane triisocyanate, 1,6,11-undecane triisocyanate, 1,8-isocyanate-4,4-isocyanate triisocyanate compounds such as trimethylolpropane, 1,3,6-hexamethylene triisocyanate, bicycloheptane triisocyanate, an adduct of trimethylolpropane and 2,4-toluylene diisocyanate, an adduct of trimethylolpropane and a diisocyanate such as 1,6-hexamethylene diisocyanate, and modified polyisocyanate compounds obtained by reacting a polyhydric alcohol such as glycerin or pentaerythritol with the above-mentioned aliphatic and aromatic diisocyanate compounds and the above-mentioned triisocyanate compounds.These may be used alone or in combination of two or more.

[0051] The amount of the crosslinking agent to be added varies depending on the molecular weight and molecular weight distribution of the polylactic acid used. When the amount of low molecular weight polylactic acid is large, a larger amount tends to be required to provide a melt strength suitable for foaming. However, since an increase in the amount of the crosslinking agent to be added tends to deteriorate the biodegradability and crystallinity, the amount of the crosslinking agent in the foamed sheet of the present invention is preferably 2% by mass or less, based on 100% by mass of the total amount of the polylactic acid and the crosslinking agent.

[0052] As other crosslinking agents, compounds having two or more oxazoline groups in the molecule, compounds having two or more carbodiimide groups in the molecule (polycarbodiimide crosslinking agents), and the like can also be used.

[0053] Other means for imparting melt strength (means for imparting melt tension) suitable for foaming include, for example, the following methods: dispersing layered silicate, fibrous foaming nucleating agent, etc. at the nano level, crosslinking a resin composition using a crosslinking agent or crosslinking assistant, crosslinking a resin composition with an electron beam, etc., adding another resin composition having high melt tension, lowering the foaming temperature, etc.

[0054] <<Other>> Other components include additives such as heat stabilizers, antioxidants, plasticizers, etc. These may be used alone or in combination of two or more.

[0055] The content of the other components is preferably 2% by mass or less based on the total amount of organic matter in the foamed sheet, which leads to better recyclability.

[0056] <Physical properties of foam sheet> <<Bulk density>> The bulk density of the foamed sheet in the present invention is 0.063 g / cm 3 More than 0.125g / cm3 When the bulk density is in this range, it can be said that a good high expansion ratio is obtained, and good strength and heat resistance are also obtained. 3 If it is less than 0.125g / cm, the heat resistance and strength will be poor. 3 Above this, the foaming ratio is inferior.

[0057] The expansion ratio can also be expressed as true density / bulk density. The smaller the bulk density (the higher the expansion ratio), the lighter the weight of the molded product can be if it has the same shape, which is preferable from the viewpoint of saving resources.

[0058] The bulk density of the foam sheet is 0.063 g / cm 3 More than 0.083g / cm 3 Within this range, a foamed sheet having an excellent balance between strength and heat resistance as a structure can be obtained.

[0059] In order to make the bulk density of the foamed sheet fall within the range of the present invention, for example, the amount of foaming agent added may be adjusted within the range described below, the amount of crosslinking agent added may be adjusted to make the melt flow rate fall within the range described below, or the temperature of the composition during foaming may be adjusted. The amount of foaming agent added is such that, as long as the amount is within the range in which the loss of foaming agent due to cell breakage does not occur, the bulk density tends to be reduced as the amount is increased, and the melt flow rate is such that, as long as the melt flow rate is within the range described below, the bulk density tends to be reduced as the amount is decreased, and the composition temperature during foaming is such that, as long as the composition does not lose fluidity due to crystallization or glass transition, the lower the temperature, the more the loss of foaming agent due to cell breakage can be suppressed, and the bulk density tends to be reduced. In addition, the melt flow rate tends to be reduced by increasing the amount of crosslinking agent added, as long as the amount is within the range described below.

[0060] The bulk density of the foamed sheet in the present invention is measured as follows. The foamed sheet is left to stand for 24 hours or more in an environment adjusted to a temperature of 23°C and a relative humidity of 50%, and a test piece of 50 mm x 50 mm is cut out. The cut test piece is subjected to a submerged weighing method using an automatic specific gravity meter (e.g., DSG-1 manufactured by Toyo Seiki Seisakusho) to determine the bulk density. The weight (g) of the foamed sheet in air is precisely weighed, and then the weight (g) of the foamed sheet in water is precisely weighed, and the bulk density is calculated according to the following formula. Bulk density [g / cm 3 ] = weight of sample in air [g] / {(weight of sample in air [g] - weight in liquid [g]) × liquid density [g / cm 3 ]}

[0061] <<Basic weight>> The basis weight of the foamed sheet in the present invention is calculated by the following formula for a foamed sheet having a uniform thickness. When the foamed sheet has a non-uniform thickness, for example, the foamed sheet is cut into a size of 5 cm x 5 cm to prepare a plate-shaped test piece, and the weight is measured to determine the basis weight [g / m 2 ] = weight of plate specimen [g] / 0.025 [m 2 In this case, three or more plate-shaped test pieces are prepared at equal intervals in the direction perpendicular to the extrusion direction of the foamed sheet, and the basis weight is determined by the average value of the values ​​obtained from the plate-shaped test pieces. Basis weight [g / m 2 ]=1000 × bulk density [g / cm 3 ] × sheet thickness [mm]

[0062] When producing bags, packaging containers, tableware, cutlery, stationery, and cushioning materials containing the foamed sheet of the present invention, the bulk density of the foamed sheet is within the range of the present invention, 0.063 g / cm. 3 More than 0.125g / cm 3 If it is less than this, the basis weight calculated using the above formula is 900g / m 2 Less than 300 g / m 2 The following foam sheet is lightweight and weighs 125g / m 2 The above foam sheets provide excellent heat insulation and are 200g / m 2 More preferably, 250 g / m2 By using the above foamed sheet, a product having excellent strength can be obtained.

[0063] <<Biodegradable>> The foamed sheet of the present invention has sufficient biodegradability, and the biodegradability can be evaluated by determining the degree of biodegradation in accordance with, for example, JIS K6953-2. The degree of biodegradation is preferably 60% or more in 6 months, and more preferably 60% or more in 45 days.

[0064] <<Volatile components>> In the present invention, it is preferable that the foamed sheet does not substantially contain any volatile components. By substantially not containing any volatile components, the dimensional stability is improved and the impact on the human body and the environment can be reduced. Examples of the volatile components that may be contained include organic solvents and foaming agents such as butane.

[0065] In the present invention, as described below, the compressive fluid, for example, carbon dioxide (CO2) or nitrogen (N2), can also function as a foaming agent. Therefore, when a compressive fluid such as carbon dioxide or nitrogen is used as both a compressive fluid and a foaming agent, these foaming agents diffuse from the foam sheet into the atmosphere immediately after production, making it easier to make the foam sheet substantially free of volatile components. "Substantially free" means that the amount is below the lower limit of detection in the following analysis.

[0066] A part of the foamed sheet is used as a sample, 2 parts by mass of 2-propanol is added to 1 part by mass of the sample, and the mixture is dispersed by ultrasonic waves for 30 minutes, and then stored in a refrigerator (5°C) for one day or more to obtain an extract of volatile components. The extract of volatile components is analyzed by gas chromatography (GC-14A, manufactured by Shimadzu Corporation) to quantitatively determine the amount of volatile components in the foamed sheet. The measurement conditions are as follows.

[0067] Equipment: Shimadzu GC-14A Column: CBP20-M 50-0.25 Detector: FID Injection volume: 1μL~5μL Carrier gas: He 2.5kg / cm 2 Hydrogen flow rate: 0.6 kg / cm 2 Air flow rate: 0.5kg / cm 2 Chart speed: 5mm / min Sensitivity: Range 101 x Atten 20 Column temperature: 40℃ Injection Temp: 150℃

[0068] That is, when the foamed sheet of the present invention is subjected to the following measurement, it is preferable that no organic compounds having a boiling point of −20° C. or more and less than 150° C. at 1 atm are detected. [measurement] A part of the foamed sheet is dispersed in a solvent, and the extract of the volatile components is measured by gas chromatography under the above-mentioned conditions to quantitatively determine the amount of the organic compounds.

[0069] In order to prevent organic compounds from being detected when the foamed sheet is subjected to the above-mentioned measurement, as described above, the foamed sheet according to this embodiment can use a foaming agent other than organic compounds such as CO2, and by doing so, for example, the content of volatile components can be made substantially 0 mass %. By making the foamed sheet into one in which no organic compounds are detected, odors and the like are not generated.

[0070] <<Average bubble diameter>> The average foam diameter of the foamed sheet in the present invention is such that the bulk density of the foamed sheet is 0.063 g / cm 3 More than 0.083g / cm 3 If it is less than 100 μm, it is preferable that the bulk density is 0.083 g / cm 3 Greater than 0.125g / cm 3 If the average foam diameter is within this range, a foamed sheet having excellent heat resistance can be obtained.

[0071] The method for measuring the average foaming diameter of the foamed sheet is not particularly limited and can be appropriately selected depending on the purpose. For example, the foamed sheet is cut in cross section using a sharp razor (e.g., Nisshin EM 76 razor), and the cross section of the foamed sheet is observed using SEM with KEYENCE VE-9800. For three cross-sectional SEM photographs (magnification 50 times) obtained, the gray components corresponding to the bubbles and the resin components (white) are binarized using image analysis software (e.g., Mediacy Image-Pro Premier), and the average foaming diameter (Ferret diameter) is obtained within a range of 1 mm x 1 mm, and the average foaming diameter is calculated for bubbles with a Ferret diameter of 0.5 μm or more.

[0072] The average bubble diameter can be adjusted by the dispersion state, melt tension, etc., but is not limited to these.

[0073] <<Average thickness>> The average thickness of the foamed sheet of the present invention is preferably 0.1 mm or more and 10 mm or less. When the average thickness is 10 mm or less, it is possible to prevent the foamed sheet from becoming difficult to mold. If the thickness is 0.1 mm or more, the strength of the structure can be ensured.

[0074] The average thickness of the foamed sheet is measured at 10 points using a caliper (for example, a Mitutoyo Digimatic Caliper) and the arithmetic average of the measured values ​​is used.

[0075] <<Crystalline>> The crystallinity of the foamed sheet can be determined from the crystalline melting peak area and the cold crystallization peak area, which are values ​​determined by differential scanning calorimetry (DSC) measurement in accordance with JIS K7122, a method for measuring the heat of transition of plastics.

[0076] For the DSC measurement, for example, a differential scanning calorimeter Q-2000 (manufactured by TA Instruments) can be used. 5 to 10 mg of a sample cut out from a foamed sheet is placed in a container of the differential scanning calorimeter, and the temperature is increased from 10°C to 200°C at a heating rate of 10°C / min. During the temperature increase, the area corresponding to the exothermic peak observed at about 80°C to 130°C is taken as the cold crystallization peak area, and the area corresponding to the endothermic peak at a higher temperature is taken as the crystal melting peak area.

[0077] However, in a foamed sheet in which crystallization has progressed sufficiently, the cold crystallization peak may not be observed, and in a foamed sheet in which crystallization has not progressed at all, the crystalline melting peak may not be observed.

[0078] In the polylactic acid foamed sheet of the present invention, the value obtained by subtracting the cold crystallization peak area from the crystalline melting peak area measured by differential scanning calorimetry (DSC) is preferably 20 J / g or more, more preferably 30 J / g or more, so that the foamed sheet can exhibit better heat resistance.

[0079] In order to make the above subtracted value 20 J / g or more, for example, the bulk density of the foamed sheet is set to 0.063 g / cm3, which is within the range of the present invention. 3 More than 0.125g / cm 3 For example, when the bulk density of the foamed sheet is 0.063 g / cm or less, and the average foam diameter is within the following range according to the bulk density. 3 More than 0.083g / cm 3 When the bulk density of the foamed sheet is 0.083 g / cm3 or more and 0.125 g / cm3 or less, the average foam diameter is preferably 100 μm or less, and when the bulk density of the foamed sheet is 0.083 g / cm3 or more and 0.125 g / cm3 or less, the average foam diameter is preferably 200 μm or less. In addition, it is preferable to add the foam nucleating agent because it can promote crystallization.

[0080] <<Weight average molecular weight>> The foamed sheet of the present invention preferably contains a crosslinked polymer obtained by reacting polylactic acid with a crosslinking agent, and in this case, the weight average molecular weight (Mw) of the crosslinked polymer (also referred to as a polylactic acid-containing crosslinked polymer) is preferably 200,000 to 400,000, more preferably 250,000 to 350,000. When the weight average molecular weight is 200,000 or more, hydrolysis resistance is improved and a decrease in molecular weight when immersed in warm water can be suppressed. In addition, when the weight average molecular weight is 400,000 or less, an increase in melt viscosity is suppressed, and the extrudability of the molten resin is improved.

[0081] The method for measuring the weight-average molecular weight of the crosslinked polymer is not particularly limited and can be appropriately selected depending on the purpose, but can be measured using gel permeation chromatography (GPC). For example, the foamed sheet is placed in a tetrahydrofuran (THF) solution and heated to 65°C to dissolve the polylactic acid. Then, the solution is filtered through a 0.45 μm membrane filter and the obtained solution is measured.

[0082] <Physical properties of the composition> The foamed sheet of the present invention preferably has a melt flow rate (MFR) of 0.3 g / 10 min to 5 g / 10 min at a test temperature of 190° C. and a load of 2.16 kg. In this case, the foamed sheet exhibits appropriate fluidity in the foaming process and is advantageous for the progress of crystallization during foaming. It is more preferable that the MFR is 3 g / 10 min or less in order to suppress bubble coalescence and bubble breakage and to control the crystallization rate.

[0083] The MFR can be measured, for example, using a Melt Flow Index Tester 120-SAS (manufactured by Yasuda Seiki Seisakusho) in accordance with JIS K7210-1:2014 "Plastics - Determination of melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastics - Part 1" Method B.

[0084] The measurement conditions are as follows. The foamed sheet is crushed by freeze-pulverization, and the resulting sample is vacuum-dried at 80°C for 4 hours before measurement. 3 to 8 g is used for the measurement, and measurements are taken three times under the following conditions: preheating: 300 seconds, load hold: 30 seconds, test temperature: 190°C, load: 2.16 kg (21.18 N). The arithmetic average of the measured values ​​is used as the MFR (g / 10 min).

[0085] (manufactured product) The foamed sheet of the present invention may be used as it is, or may be used as a product. The sheet of the present invention is excellent in lightness and heat resistance, so it is suitable for use as a food container or tableware. It is also suitable as a heat-resistant food container, but is not limited to such uses. The foamed sheet of the present invention may be used as it is after printing, etc.

[0086] The product using the foamed sheet of the present invention is not particularly limited and can be appropriately changed. The foamed sheet of the present invention may be processed to produce a product, or the foamed sheet of the present invention and other components may be used to produce a product. The other components are not particularly limited as long as they are used in ordinary resin products, and can be appropriately selected depending on the purpose.

[0087] The processing of the foamed sheet of the present invention is not particularly limited, and may be, for example, subjected to a process of processing using a mold to obtain a product. The processing method of the sheet using a mold is not particularly limited, and a conventionally known method for thermoplastic resins may be used, for example, vacuum molding, pressure molding, vacuum pressure molding, press molding, etc.

[0088] Examples of the manufactured products (also called "consumer goods") include daily necessities such as bags, packaging containers, trays, tableware, cutlery, stationery, and cushioning materials. The concept of manufactured products includes intermediates for processing manufactured products, such as rolled sheets and single manufactured products, as well as parts made of manufactured products, such as handles for trays, and products equipped with manufactured products, such as trays with handles attached. Examples of the bags include plastic bags, shopping bags, and garbage bags. Examples of the stationery include clear files and badges.

[0089] Conventional foam sheets had large bubble diameters and large variations in size, which led to issues with the sheet's physical properties such as strength and flexibility. Since the products molded using the foamed sheet of the present invention have excellent physical properties, they can be used for purposes other than the above-mentioned daily necessities, for example, they can be widely used as sheets, packaging materials, etc. for industrial materials, agricultural products, food, pharmaceuticals, cosmetics, etc. The foamed sheet of the present invention is useful in applications where the biodegradability of the foamed sheet can be utilized, particularly as a packaging material for food, and as a medical sheet for cosmetics, medicines, etc., and further improved performance can be expected by reducing the thickness, etc.

[0090] <Molded body> In addition, a molded article may be used as an example of the product. The molded article of the present invention is characterized by being obtained by thermoforming the foamed sheet of the present invention. The molded article of the present invention has good biodegradability, and is also excellent in lightness and heat resistance. The thermoforming temperature is not particularly limited, but is preferably, for example, 60° C. or higher and 300° C. or lower.

[0091] (Method of manufacturing foam sheet) The method for producing a foamed sheet of the present invention includes a kneading step, a foaming step, and, if necessary, other steps. The kneading step and the foaming step may be carried out simultaneously or separately.

[0092] <Mixing process> The kneading step is a step of kneading polylactic acid in the presence of a compressive fluid at a temperature lower than the melting point of the polylactic acid to obtain a composition. In addition, it is preferable that either the D-form or the L-form of lactic acid constituting the polylactic acid is 98 mol % or more in the polylactic acid. It is preferable that it is more than 98 mol %.

[0093] In the kneading step, it is preferable to use a filler, which can improve heat resistance. When a filler is used, the polylactic acid and the filler are kneaded at a temperature lower than the melting point of the polylactic acid to obtain a composition.

[0094] In the kneading step, it is preferable to use a crosslinking agent. Although not particularly limited, when a crosslinking agent is used, polylactic acid is kneaded in the presence of a compressive fluid to obtain a composition precursor, and then the crosslinking agent is added to the composition precursor in the presence of a compressive fluid and kneaded to obtain a composition.

[0095] When a filler and a crosslinking agent are used in the kneading step, the polylactic acid, the filler, and the crosslinking agent may be kneaded simultaneously to obtain a composition, or the polylactic acid and the filler may be kneaded to obtain a composition precursor, and the crosslinking agent may be added to the composition precursor to obtain a composition.

[0096] The composition in this embodiment contains polylactic acid, and optionally contains a filler, a crosslinking agent, etc., and refers to a state before foaming. Since the composition contains polylactic acid, it may be called a polylactic acid composition. The composition precursor may be called a master batch, and the composition precursor may be processed, for example, by pelletizing, and may be called a master batch.

[0097] The polylactic acid, filler, and crosslinking agent that can be used in the kneading step are those described above, and therefore a description thereof will be omitted.

[0098] <<Compressible fluid>> Aliphatic polyesters such as polylactic acid have a tendency to rapidly decrease in melt viscosity after the melting point, so when fillers are mixed in, they tend to aggregate, which is particularly noticeable when the fillers are small in size.

[0099] In the present invention, polylactic acid is kneaded in the presence of a compressive fluid. By kneading using a compressive fluid, when a filler is used, the filler can be easily uniformly dispersed in the polylactic acid. The reason why it is preferable to use a compressive fluid to knead the filler and polylactic acid and uniformly disperse the foaming nucleating agent will be described below.

[0100] It is generally known that resins impregnated with compressible fluids have a lower melt viscosity (see "Latest Application Technology of Supercritical Fluids" by NTS). However, in the kneading process, a resin with a higher melt viscosity can apply higher shear stress to the foam nucleating agent, making it easier to break down agglomerates, and is therefore considered preferable from the standpoint of dispersion. Therefore, the decrease in the melt viscosity of the resin due to the impregnation of the compressible fluid seems to contradict the improvement of the kneadability. In fact, in general filler kneading, pressure is applied without using a compressible fluid, but this is aimed at decreasing the free volume of the resin and increasing the interaction between the resins (increasing the viscosity), and plasticizing the resin has the opposite effect on the kneadability (see "K. Yang. R. Ozisik R. Polymer, 47.2849 (2006)").

[0101] However, the present inventors have intensively studied whether compressive fluids can be used for kneading polylactic acid, particularly for kneading polylactic acid with a filler, and have found that in the presence of a compressive fluid, if the temperature is lower than the melting point of polylactic acid, the viscosity of polylactic acid can be made suitable for kneading, and the filler can be uniformly dispersed. Up until now, when kneading polylactic acid with a foaming nucleating agent, kneading was only possible in a low melt viscosity range equal to or higher than the melting point of polylactic acid, whereas in the present invention, kneading can be performed in a high viscosity state at a temperature lower than the melting point of polylactic acid using a compressive fluid, thereby further improving the dispersibility of the foaming nucleating agent.

[0102] In addition, the compressive fluid can also function as a foaming agent depending on the type, etc. A foaming agent is usually used when producing a foamed sheet, but when a compressive fluid such as carbon dioxide or nitrogen is used as a foaming agent in the production of a foamed sheet made of a polylactic acid composition, kneading and foaming can be carried out in a continuous process, which is preferable as a production form from the viewpoint of reducing the environmental load.

[0103] Substances that can be used in a compressible fluid state include, for example, carbon monoxide, carbon dioxide, nitrous oxide, nitrogen, methane, ethane, propane, 2,3-dimethylbutane, ethylene, dimethyl ether, etc. Among these, carbon dioxide is preferable because it has a critical pressure of about 7.4 MPa and a critical temperature of about 31° C., and can easily create a supercritical state, is non-flammable, and is easy to handle. These compressible fluids may be used alone or in combination of two or more types.

[0104] Here, the compressible fluid used in this embodiment will be described with reference to Figs. 1 and 2. Fig. 1 is a phase diagram showing the state of a substance with respect to temperature and pressure. Fig. 2 is a phase diagram for defining the range of compressible fluids. In this embodiment, "compressible fluid" refers to a state in which a substance exists in any of the regions (1), (2), and (3) shown in Fig. 2 in the phase diagram shown in Fig. 1.

[0105] In such a region, the substance's density becomes extremely high and it is known that the substance behaves differently from that at normal temperature and pressure. When a substance exists in region (1), it becomes a supercritical fluid. A supercritical fluid is a fluid that exists as a non-condensable high-density fluid in a temperature and pressure region exceeding the limit (critical point) at which gas and liquid can coexist, and does not condense even when compressed. When a substance exists in region (2), it becomes a liquid, but it is a liquefied gas obtained by compressing a substance that is in a gaseous state at room temperature (25°C) and normal pressure (1 atm). When a substance exists in region (3), it is in a gaseous state, but it is a high-pressure gas with a pressure of 1 / 2 (1 / 2Pc) or more of the critical pressure (Pc).

[0106] The solubility of the compressive fluid changes depending on the combination of the resin type and the compressive fluid, the temperature, and the pressure, so the supply amount of the compressive fluid needs to be adjusted appropriately. For example, in the case of a combination of polylactic acid and carbon dioxide, when the composition (including polylactic acid and, if necessary, a filler, a crosslinking agent, etc.) is taken as 100 parts by mass, the supply amount of carbon dioxide is preferably 2% by mass or more and 30% by mass or less. If the supply amount of carbon dioxide is 2% by mass or more, the problem that the effect of plasticization is limited can be prevented. If the supply amount of carbon dioxide is 30% by mass or less, the problem that the carbon dioxide and polylactic acid undergo phase separation and a foamed sheet of uniform thickness cannot be obtained can be prevented.

[0107] Among these, it is preferable to use compressive fluids such as carbon dioxide and nitrogen. As described above, it is preferable that the obtained foamed sheet does not substantially contain volatile components, and it is preferable that the foamed sheet does not substantially contain organic compounds having a boiling point of -20°C or more and less than 150°C. Note that "substantially not contained" is as described in the section on volatile components in the physical properties of the foamed sheet. A compressive fluid such as carbon dioxide or nitrogen functions as a foaming agent, and by not using a foaming agent as a volatile component, it is possible to obtain a foamed sheet that is odorless and safer to handle.

[0108] <<Other foaming agents>> Other foaming agents may be used in addition to the compressive fluid. Examples of other foaming agents include physical foaming agents such as hydrocarbons such as lower alkanes, such as propane, normal butane, isobutane, normal pentane, isopentane, and hexane, ethers such as dimethyl ether, halogenated hydrocarbons such as methyl chloride and ethyl chloride, and compressible gases, such as carbon dioxide and nitrogen, which are easily capable of producing a foamed sheet with a high expansion ratio. As described above, it is preferable to use a compressible fluid such as carbon dioxide or nitrogen as the foaming agent.

[0109] <<Kneading equipment>> The kneading apparatus used in the production of the polylactic acid composition may be a continuous process or a batch process, but it is preferable to select an appropriate reaction process taking into consideration the efficiency of the apparatus, the characteristics and quality of the product, etc.

[0110] As the kneading device, a single-screw extruder, a twin-screw extruder, a kneader, a cage-type stirring tank without an axis, a Vivolac manufactured by Sumitomo Heavy Industries, Ltd., an N-SCR manufactured by Mitsubishi Heavy Industries, Ltd., a tubular polymerization tank equipped with a spectacle blade, lattice blade, Kenix type, or Sulzer type SMLX type static mixer manufactured by Hitachi, Ltd., and the like can be used in terms of the viscosity suitable for kneading. In terms of color tone, a finisher, N-SCR, a twin-screw extrusion ruder, and the like, which are self-cleaning polymerization devices, can be mentioned. Among these, the finisher and N-SCR are preferred in terms of production efficiency, color tone of the resin, stability, and heat resistance.

[0111] An example of a kneading device is shown in FIG. 3. As the illustrated continuous kneading device 100, for example, a twin-screw extruder (manufactured by JSW) can be used. For example, the screw diameter is 42 mm, and L / D=48. In this example, raw materials such as polylactic acid and filler are supplied from a first supply unit 1 and a second supply unit 2 to a raw material mixing / melting area a, and mixed and melted. The mixed and melted raw materials are supplied with a compressive fluid by a compressive fluid supply unit 3 in a compressive fluid supply area b. Then, the raw materials are kneaded in a kneading area c. Then, the compressive fluid is removed in a compressive fluid removal area d, and the raw materials are made into, for example, pellets in a molding processing area e. In this way, a master batch can be produced as a composition precursor.

[0112] The compressible fluid (liquid material) is supplied, for example, by a metering pump, and solid raw materials such as resin pellets and filler are supplied, for example, by a fixed-volume feeder.

[0113] -Raw material mixing and melting area- In the raw material mixing and melting area, resin pellets and fillers are mixed and heated. The heating temperature is set to a temperature higher than the melting temperature of the resin, and in the subsequent area where the compressible fluid is supplied, the resin is made to be uniformly mixed with the compressible fluid.

[0114] -Compressible fluid supply area- Once the resin pellets have been heated and are in a molten state, a compressive fluid is supplied to plasticize the molten resin.

[0115] -Mixing area- The temperature of the kneading area is set so that the viscosity is suitable for kneading the filler. The set temperature varies depending on the specifications of the reactor, the type of resin, the structure of the resin, the molecular weight, etc., so there is no particular limitation and it can be changed as appropriate. For example, in the case of commercially available polylactic acid with a weight average molecular weight (Mw) of about 200,000, kneading is usually performed at a temperature of 10°C to 20°C above the melting point of polylactic acid.

[0116] In contrast, the present invention is characterized by kneading at a temperature lower than the melting point of polylactic acid, and can knead at a relatively high viscosity at a temperature lower than the melting point. Specifically, the temperature is 0°C to -60°C from the melting point, more preferably -10°C to -40°C. In a simple manner, the temperature can be set based on the current value of the stirring power of the device, but these set values ​​are usually in a range that cannot be reached without the present invention.

[0117] <<Foam sheet making equipment>> Next, a foam sheet is produced by a foam sheet forming apparatus. As the foam sheet forming apparatus, for example, the apparatus exemplified as the kneading apparatus above can be used. The kneading apparatus and the foam sheet forming apparatus may be integrated into one apparatus, or may be separate apparatuses.

[0118] An example of a foamed sheet forming apparatus is shown in Fig. 4. As the continuous foamed sheet forming apparatus 110, for example, a twin-screw extruder can be used as described above. In the continuous foamed sheet forming apparatus 110, for example, raw materials such as a master batch, polylactic acid, and a crosslinking agent are supplied from a first supply unit 1 and a second supply unit 2 to a raw material mixing / melting area a, where they are mixed and melted. A compressible fluid is supplied to the mixed and melted raw materials by a compressible fluid supply unit 3 in a compressible fluid supply area b.

[0119] The mixture is then kneaded in the kneading area c to obtain a composition. The mixture is then fed to the heating area d, where it is heated and kneaded, and then extrusion-foamed, for example, by opening it to the atmosphere. The extrusion-foamed foam sheet 4 is wound around a mandrel.

[0120] In the continuous foamed sheet forming apparatus 110, the raw material mixing / melting area a, the compressible fluid supplying area b, and the kneading area c are also referred to as a first extruder, and the heating area d is also referred to as a second extruder. In this example, the mixed, melted, and kneaded raw materials are extruded by the first extruder to the second extruder, and a foamed sheet is extruded and foamed by the second extruder. For example, a circular die can be used in the second extruder.

[0121] In this example, the kneading step is performed by the kneading device and the first extruder of the foam sheet forming device, and the foaming step described below is performed by the second extruder of the foam sheet forming device. However, the present invention is not limited to this configuration. For example, the areas where the kneading step and the foaming step are performed can be changed as appropriate.

[0122] <Foaming process> The foaming step is a step in which the compressive fluid is removed to foam the composition (polylactic acid composition). The compressive fluid is gradually replaced by air in the atmosphere and can be removed from the foamed sheet. For example, the compressive fluid can be removed by exposing the composition to the atmosphere. The temperature during the foaming step is preferably heated to near the melting point of the polylactic acid resin.

[0123] In the foaming process, it is understood that the compressive fluid dissolved in the composition forms foam nuclei mainly at the interface with the filler in response to an operation of reducing the solubility of the compressive fluid and making it supersaturated by reducing the pressure or heating, and the compressive fluid dissolved in the composition diffuses into the foam nuclei, causing the foam nuclei to grow into bubbles, thereby obtaining a foam. Since foaming starts from the filler, a foamed sheet having uniform and fine bubbles can be produced only when the filler is uniformly dispersed in the polylactic acid. Even if a filler is not used, a foamed sheet having uniform and fine bubbles can be produced because a small amount of crystals generated in the kneading area essentially acts as a foam nucleating agent. However, if crystallization proceeds excessively, the fluidity of the composition is reduced, and foaming itself may become difficult, so it is preferable to add a foam nucleating agent.

[0124] <Other processes> The other steps are not particularly limited and include steps that are usually performed in the production of foamed sheets, such as a molding step for processing into a sheet. Examples of the forming step include vacuum forming, pressure forming, press forming, etc. A sheet molded product is obtained by the forming step. Also, a step of thermoforming a foamed sheet into a molded product is also included. EXAMPLES

[0125] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples. In addition, Examples 1, 2, 5, 6, 7, 8, 10, and 11 refer to Reference Examples 1, 2, 5, 6, 7, 8, 10, and 11 which are not included in the present invention.

[0126] Example 1 <Preparation of foam sheet> <<Masterbatch production>> Using the continuous kneading device 100 shown in Fig. 3, 9.7 kg / hr of polylactic acid (REVODE190, manufactured by HISUN Co., Ltd.), 0.3 kg / hr of silica (QSG-30, manufactured by Shin-Etsu Chemical Co., Ltd.) as a filler, and 0.99 kg / h of carbon dioxide as a compressive fluid (equivalent to 10% by mass relative to polylactic acid) were supplied to the compressive fluid supply area b, and kneading was performed in the kneading area c. Next, the compressive fluid was removed in the compressive fluid removal area d. This produced a polylactic acid composition precursor containing 3% by mass of filler. Next, in the molding processing area e, the polylactic acid composition precursor containing 3% by mass of filler was extruded into a water bath in the form of strands, and after cooling with water, pelletized with a strand cutter. This resulted in a master batch containing 3% by mass of filler (3% by mass filler master batch) as the composition precursor.

[0127] The temperatures in each zone were as follows: Raw material mixing / melting area a and compressible fluid supply area b: 190℃ Mixing area c: 150℃ Compressible fluid removal area d: 190℃ Molding processing area e: 190℃

[0128] The pressure in each zone was as follows: From compressible fluid supply area b to mixing area c: 7.0 MPa Compressible fluid removal area d: 0.5MPa

[0129] <<Making foam sheets>> In the continuous foam sheet forming apparatus 110 shown in FIG. 4, 1.67 kg / hr of [3 mass% filler master batch] and 8.33 kg / hr of polylactic acid (REVODE190, manufactured by HISUN) were supplied to the raw material mixing and melting area a of the first extruder so that the filler content was 0.5 mass% relative to the total amount of polylactic acid and foam nucleating agent. Next, 0.05 kg / hr of epoxy-based crosslinking agent (BASF Joncryl 4368C) (equivalent to 0.5 mass parts when the total amount of polylactic acid and foam nucleating agent is 100 mass parts) was supplied to the raw material mixing and melting area a of the first extruder. Next, 0.99 kg / h of carbon dioxide (equivalent to 10 mass% relative to the total amount of polylactic acid, foam nucleating agent, and crosslinking agent) was supplied to the compressible fluid supply area b of the first extruder. These were mixed, melted, kneaded, and supplied to the second extruder.

[0130] Then, the mixture was kneaded in the heating area d of the second extruder to obtain a composition (polylactic acid composition). The composition was then discharged from a circular die with a slit aperture of 70 mm attached to the tip of the second extruder at a discharge rate of 10 kg / h, cooled to a resin temperature of 150° C., and exposed to the atmosphere to be extruded and foamed. The extruded and foamed cylindrical polylactic acid-based resin foam sheet was placed on a cooled mandrel, and the outer surface was cooled by blowing air from an air ring, and the sheet was cut open with a rotary blade cutter to obtain a flat sheet-like foam. In this way, the polylactic acid foam sheet of this example was produced.

[0131] The temperatures in each zone were as follows: First extruder raw material mixing and melting area a: 190℃ Compressive fluid supply area b of the first extruder: 190°C Mixing area of ​​the first extruder c: 150℃ Heating area of ​​the second extruder d: 140°C

[0132] The pressure in each zone was as follows: Compressible fluid supply area b of the first extruder: 7.0 MPa First extruder mixing area c: 7.0MPa Heating area of ​​the second extruder d: 7.0MPa

[0133] The physical properties of the obtained polylactic acid foam sheet are shown in Table 1. In Table 1, the proportion of polylactic acid and the proportion of crosslinking agent in the organic component are based on the above recipe. In other words, they are calculated from the proportions of the charged materials. In addition, the L-form ratio was used to confirm whether the mol% of D-form or L-form of lactic acid constituting the polylactic acid satisfies the range of the present invention. The same applies to Tables 2 and 3.

[0134] Example 2 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that in place of the [3 mass% filler master batch], polylactic acid (REVODE190, manufactured by HISUN Corporation) was used and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 1.

[0135] Example 3 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amount of crosslinking agent was changed as shown in Table 1, the heating area d of the second extruder was set to 150°C, and the lip distance of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 1.

[0136] Example 4 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amount of crosslinking agent was changed as shown in Table 1, the heating area d of the second extruder was set to 155°C, and the lip distance of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 1.

[0137] Example 5 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the crosslinking agent type was changed to an isocyanate-based crosslinking agent (Asahi Kasei Corporation, Duranate TPA-100) and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value in Table 1.

[0138] Example 6 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that in the preparation of the master batch of Example 1, the silica filler was replaced with titanium oxide (TTO-55(C), manufactured by Ishihara Sangyo Kaisha, Ltd.) and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 1.

[0139] Example 7 A polylactic acid foam sheet was produced in the same manner as in Example 1, except that LX-575 (manufactured by Corbion) was used as the polylactic acid type and the lip spacing of the circular die was changed so that the thickness of the foam sheet would be the value shown in Table 2.

[0140] Example 8 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the ratio of [3 mass% filler master batch] to polylactic acid (REVODE190, manufactured by HISUN Corporation) was changed and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 2.

[0141] Example 9 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amount of crosslinking agent was changed as shown in Table 2 and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 2.

[0142] Example 10 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the lip distance of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 2.

[0143] Example 11 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amount of crosslinking agent was changed as shown in Table 2 and the lip distance of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 2.

[0144] Example 12 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amounts of crosslinking agent and foam nucleating agent were changed as shown in Table 2 and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 2.

[0145] Comparative Example 1 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that polylactic acid (REVODE190, manufactured by HISUN Corporation) was used instead of the [3 mass% filler master batch] in Example 1, no crosslinking agent was used, and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 3.

[0146] Comparative Example 2 A polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the heating area d of the second extruder was set to 155°C and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 3.

[0147] Comparative Example 3 In Comparative Example 3, a polylactic acid foamed sheet was produced in the same manner as in Example 1, except that the amount of crosslinking agent was changed as shown in Table 3 and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 3.

[0148] Comparative Example 4 In Comparative Example 4, a polylactic acid foamed sheet was produced in the same manner as in Example 1, except that REVODE110 (manufactured by HISUN) was used as the polylactic acid and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 3.

[0149] Comparative Example 5 In Comparative Example 5, a polylactic acid foamed sheet was produced in the same manner as in Example 1, except that LX-175 (manufactured by Corbion) was used as the polylactic acid, the second extruder heating area d was set to 130°C, and the lip spacing of the circular die was changed so that the thickness of the foamed sheet would be the value shown in Table 3.

[0150] Comparative Example 6 In Comparative Example 6, a polylactic acid foam sheet was produced in the same manner as in Example 1, except that L-175 (manufactured by Corbion) was used instead of REVODE190 (manufactured by HISUN) as the polylactic acid, and the lip spacing of the circular die was changed so that the thickness of the foam sheet would be the value in Table 3.

[0151] (Measurement and Evaluation) The obtained foamed sheet was measured for bulk density, biodegradability, amount of volatile substances, average foam diameter, average thickness, degree of crystallization, MFR, and heat resistance. The measurement results are shown in Tables 1 to 3.

[0152] <Bulk density> The foamed sheet is left to stand for 24 hours or more in an environment adjusted to a temperature of 23°C and a relative humidity of 50%, and a test piece of 50 mm x 50 mm is cut out. The cut test piece is subjected to a liquid weighing method using an automatic specific gravity meter (e.g., DSG-1 manufactured by Toyo Seiki Seisakusho) to determine the bulk density. In the liquid weighing method, the weight (g) of the foamed sheet in air is precisely weighed, and then the weight (g) of the foamed sheet in water is precisely weighed, and the bulk density is calculated according to the following formula. Bulk density [g / cm 3 ] = weight of sample in air [g] / {(weight of sample in air [g] - weight in liquid [g]) × liquid density [g / cm 3 ]}

[0153] <Biodegradable> Biodegradability was evaluated by determining the degree of biodegradability in accordance with JIS K6953-2. The evaluation criteria were as follows:

[0154] [Evaluation Criteria] ◎: Biodegradability of 60% or more in 45 days 〇: Biodegradability of 60% or more in 6 months ×: Less than 60% biodegradation in 6 months

[0155] <Amount of volatile components> The foamed sheet was cut into 5 mm squares and used as a sample. 2 parts by mass of 2-propanol was added to 1 part by mass of this sample, and the sample was dispersed by ultrasonic waves for 30 minutes, and then stored in a refrigerator (5°C) for one day or more to obtain a 2-propanol extract of volatile components. The 2-propanol extract of volatile components was analyzed under the following conditions using a gas chromatograph (GC-14A, manufactured by Shimadzu Corporation) to quantify the volatile components in the foamed sheet. The measurement conditions are as follows. If the quantified volatile components were below the detection limit, that is, if the volatile components were not detected in this measurement, it was marked as "◯", and if they were detected, it was marked as "X".

[0156] Equipment: Shimadzu GC-14A Column: CBP20-M 50-0.25 Detector: FID Injection volume: 1μL~5μL Carrier gas: He 2.5kg / cm 2 Hydrogen flow rate: 0.6 kg / cm 2 Air flow rate: 0.5kg / cm 2 Chart speed: 5mm / min Sensitivity: Range 101 x Atten 20 Column temperature: 40℃ Injection Temp: 150℃

[0157] <Average bubble diameter> The cross section of the obtained foamed sheet was cut using a 76 razor manufactured by Nissin EM Co., Ltd., and the cross section of the foamed sheet was observed using a SEM with a VE-9800 manufactured by KEYENCE Corporation. For three obtained cross-sectional SEM photographs (magnification 50 times), the gray components corresponding to the bubbles and the resin components (white) were binarized using image analysis software (Image-Pro Premier manufactured by mediacy Co., Ltd.), and the average foam diameter (Ferret diameter) was obtained within an area of ​​1 mm x 1 mm, and the average foam diameter was calculated for bubbles with a Ferret diameter of 0.5 μm or more. It is preferable that the average foam diameter satisfies the following range.

[0158] The bulk density of the foam sheet is 0.063g / cm 3When it is 0.083 g / cm or more 3 and 100 μm or less when it is below the bulk density of the foamed sheet is 0.083 g / cm 3 and more than 0.125 g / cm 3 and 200 μm or less when it is below

[0159] <Average thickness> The average thickness of the foamed sheet was measured using a Mitutoyo digital caliper, and the arithmetic mean of 10 measurement values was used.

[0160] <Ratio of L-form and D-form> The obtained foamed sheet was cryogenically pulverized, 200 mg of the powder of the foamed sheet was taken into an Erlenmeyer flask, 30 ml of 1N aqueous sodium hydroxide solution was added, and the mixture was heated to 65 °C while shaking the Erlenmeyer flask to completely dissolve the polylactic acid. Subsequently, the pH was adjusted to 7 using 1N hydrochloric acid, and the solution was diluted to a predetermined volume using a volumetric flask to obtain a polylactic acid solution. Next, after filtering the above polylactic acid solution through a 0.45 μm membrane filter, based on the chart obtained by analysis using a liquid chromatograph, the area ratio was calculated from the peaks derived from the D-form and L-form, and the D-form amount ratio and L-form amount ratio were calculated as the abundance ratio. The arithmetic mean value of the results obtained by performing the above operation three times was taken as the D-form amount ratio and L-form amount ratio of the polylactic acid-based resin.

[0161] The measuring apparatus and measuring conditions are as follows. HPLC apparatus (liquid chromatography): Product name "PU-2085Plus type system" manufactured by JASCO Corporation Column: Product name "SUMICHIRAL OA5000" (4.6 mm φ × 250 mm) manufactured by Sumika Analysis Service, Ltd. Column temperature: 25 °C Mobile phase: A mixed solution of 2 mM CuSO4 aqueous solution and 2-propanol (CuSO4 aqueous solution: 2-propanol (volume ratio) = 95:5) Mobile phase flow rate: 1.0 milliliter / minute Detector: UV254 nm Injection volume: 20 microliters

[0162] <Degree of crystallization> The crystal melting peak area and the cold crystallization peak area were determined in accordance with JIS K 7122, the method for measuring the heat of transition of plastics. DSC measurements were performed using a differential scanning calorimeter, Model Q-2000 (manufactured by TA Instruments), under the following conditions.

[0163] Sample size: 5-10mg Measurement temperature range: 10℃~200℃ Heating rate: 10℃ / min Purge gas: Nitrogen, flow rate 50mL / min

[0164] <MFR(メルトフローレート)> The obtained foamed sheet was crushed by freeze crushing, and the obtained sample was vacuum dried at 80°C for 4 hours and subjected to measurement. The measurement was performed using a Melt Flow Index Tester 120-SAS (manufactured by Yasuda Seiki Seisakusho) according to JIS K7210-1:2014 "Plastics - Determination of melt mass flow rate (MFR) and melt volume flow rate (MVR) of thermoplastic plastics - Part 1" Method B. The measurement was performed three times, and the arithmetic average of the measured values ​​was used as the MFR (g / 10 min).

[0165] Sample size: 3-8g Preheat: 300 seconds Load Hold: 30 seconds Test temperature: 190℃ Load capacity: 2.16kg (21.18N)

[0166] <Molecular weight> The resulting foamed sheet was subjected to the following measurements. Equipment: GPC (Tosoh Corporation) Detector: RI Measurement temperature: 40℃ Mobile phase: Tetrahydrofuran Flow rate: 0.6mL / min.

[0167] The obtained foamed sheet was placed in a tetrahydrofuran (THF) solution and heated to 65°C to dissolve the polylactic acid. The solution was then filtered through a 0.45 µm membrane filter, and the weight average molecular weight of the polylactic acid-containing crosslinked polymer contained in the foamed sheet was measured. The number average molecular weight (Mn), weight average molecular weight (Mw), and molecular weight distribution (Mw / Mn) are the number average molecular weight, weight average molecular weight, and molecular weight distribution measured by GPC (gel permeation chromatography) using a calibration curve prepared from polystyrene samples of known molecular weight as the standard. The column used was four TSKgel SuperHM-N (manufactured by Tosoh Corporation) columns connected in series.

[0168] <Heat resistance> The storage modulus G'(25°C) at room temperature (25°C) and the storage modulus G'(80°C) at 80°C simulating boiling water were measured for the obtained foamed sheet under the following conditions, and the sheet was evaluated according to the following evaluation criteria.

[0169] [Evaluation Criteria] ◎: G'(80℃) is 1 / 10 or more of G'(25℃) ○: G'(80℃) is 1 / 50 or more and less than 1 / 10 of G'(25℃) ×: G'(80℃) is less than 1 / 50 of G'(25℃)

[0170] The measurement conditions for the foamed sheet were as follows. Sample shape: The foam sheet was cut into strips 50 mm long and 10 mm wide and used for measurement. Equipment: TA Instruments "ARES-G2" Fixture: Rectangular torsion fixture Deformation mode: Vibration Amplitude: Variable between 0.05% and 1%, feedback controlled so that the torque does not exceed 200mN·m ·Angular frequency: 6.28rad / sec Measurement temperature range: 20℃~200℃ Heating rate: 5℃ / min

[0171] <Hydrolysis resistance> The foam sheet is immersed in 95°C hot water for 5 hours, and a sample is taken to remove the moisture, after which the weight average molecular weight is measured by GPC. The weight average molecular weight is measured as described in <Molecular Weight>. The weight average molecular weight retention rate (weight average molecular weight retention rate = weight average molecular weight after immersion in water / weight average molecular weight before immersion in water x 100) is calculated from the weight average molecular weight before and after immersion in water, and classified according to the following evaluation criteria.

[0172] [Evaluation Criteria] ○: greater than 75% and less than or equal to 100% △: More than 50% and less than 75% ×: Less than 50%

[0173] [Table 1]

[0174] [Table 2]

[0175] [Table 3]

[0176] As shown in the above examples, the foamed sheet of the present invention can achieve both heat resistance and a high expansion ratio while having sufficient biodegradability. The heat resistance of the foamed sheet is evaluated based on the average expansion diameter in addition to the heat resistance of the foamed sheet. The smaller the average expansion diameter of the foamed sheet, the smaller the thermal conductivity of the foamed sheet, and the heat resistance of the foamed sheet tends to improve. For example, in Comparative Example 1, the heat resistance of the foamed sheet is evaluated as "good", but the average expansion diameter is outside the preferred range, so the heat resistance of the foamed sheet is not satisfactory. In Comparative Examples 1 to 3, the bulk density is large, and it is understood that foamed sheets with good expansion ratios are not obtained. In Comparative Example 2, the expansion ratio is insufficient, so that elongation crystallization accompanying expansion does not occur much, resulting in a low crystallization degree (18 J / g) and poor heat resistance. In Comparative Example 6, the bulk density of the foamed sheet is outside the range, and it is understood that a highly foamed sheet cannot be obtained.

[0177] (Example 13) The foamed sheet obtained in Example 1 was thermoformed in a match mold type molding machine equipped with upper and lower preheaters and molds to obtain a molded article of this Example. The temperature of the preheater was set to 250°C, and after preheating for 20 seconds, the foamed sheet was sandwiched between molds set at 80°C to perform thermoforming. For the molded article obtained in this example, the rate of area change when immersed in boiling water was determined as follows. For the molded product of this example that had been left for 24 hours or more in an environment with a temperature of 23°C and a relative humidity of 50%, a portion where the top and bottom surfaces were parallel was cut out to be a square of 5 cm in length and 5 cm in width to prepare a sample, which was then immersed in 300 ml of boiling water at 92°C for 3 minutes. After that, the area of ​​the sample that had been left for 1 hour in an environment with a temperature of 23°C and a relative humidity of 50% was measured, and the area change rate was calculated by the following formula. Area change rate = {(area before heating storage - area after heating storage) / area before heating storage} x 100 The area change rate of the molded body obtained in this example was 6%, which was a good result.

[0178] Comparative Example 7 A molded product was produced from the foamed sheet obtained in Comparative Example 3 in the same manner as in Example 13, and the same evaluation as in Example 13 was performed. The area change rate was 15%, which was inferior to the result of Example 13. [Explanation of symbols]

[0179] 1. First Supply Section 2. Second Supply Section 3. Compressible fluid supply section 4. Foam Sheet 100 Continuous kneading device 110 Continuous foam sheet making equipment [Prior art documents] [Patent documents]

[0180] [Patent Document 1] JP 2007-46019 A [Patent Document 2] Patent No. 5207277 [Patent Document 3] Patent No. 5454137 [Patent Document 4] JP 2006-328225 A [Patent Document 5] JP 2004-244457 A [Patent Document 6] Special Publication No. 2015-514819 [Patent Document 7] JP 2012-017393 A [Patent Document 8] JP 2010-247510 A [Patent Document 9] JP 2013-199640 A [Patent Document 10] JP2012-77151A

Claims

1. A foamed sheet made of a composition containing polylactic acid, The polylactic acid contains 98 mol % or more of either the D-form or the L-form of lactic acid constituting the polylactic acid, The polylactic acid is 98% by mass or more based on the total amount of organic matter in the foamed sheet, The bulk density of the foamed sheet is 0.065 g / cm 3 0.085g / cm or more 3 is as follows: The foam sheet contains an epoxy-based crosslinking agent, The foamed sheet, wherein the epoxy-based crosslinking agent accounts for 1.3 mass % or more and 1.7 mass % or less of an organic component amount in the foamed sheet.

2. 2. The foamed sheet according to claim 1, wherein the foamed sheet has a melt flow rate of 0.3 g / 10 min or more and 5 g / 10 min or less at a test temperature of 190° C. and a load of 2.16 kg.

3. 3. The foamed sheet according to claim 1, wherein the value obtained by subtracting the cold crystallization peak area from the crystalline melting peak area measured by differential scanning calorimetry (DSC) is 20 J / g or more.

4. The foamed sheet according to any one of claims 1 to 3, characterized in that, when the foamed sheet is subjected to the following measurement, no organic compound having a boiling point at 1 atm of -20°C or more and less than 150°C is detected. [measurement] A part of the foamed sheet is dispersed in a solvent, and the supernatant of the dispersion is measured by gas chromatography to determine the amount of the organic compound.

5. The foamed sheet according to any one of claims 1 to 4, wherein the foamed sheet has an average thickness of 0.1 mm or more and 10 mm or less.

6. The foam sheet contains a crosslinked polymer obtained by reacting polylactic acid with a crosslinking agent, The foamed sheet according to any one of claims 1 to 5, wherein the crosslinked polymer has a weight average molecular weight of 250,000 to 350,000.

7. A product comprising the foamed sheet according to any one of claims 1 to 6.

8. 8. The product according to claim 7, which is at least one selected from the group consisting of bags, packaging containers, tableware, cutlery, stationery, and cushioning materials.

9. A molded article obtained by thermoforming the foamed sheet according to any one of claims 1 to 6.

10. A kneading step of kneading polylactic acid in the presence of a compressive fluid at a temperature lower than the melting point of the polylactic acid to obtain a composition; and a foaming step of removing the compressive fluid to foam the composition, A method for producing a foamed sheet, wherein the foamed sheet is the foamed sheet according to any one of claims 1 to 6.

11. The method for producing a foamed sheet according to claim 10, wherein the compressive fluid is carbon dioxide.

12. The method for producing a foamed sheet according to claim 10 or 11, wherein the kneading step includes kneading the polylactic acid with a filler.

13. The method for producing a foamed sheet according to claim 12, wherein the kneading step includes kneading the polylactic acid, a filler, and a crosslinking agent.

14. The method for producing a foamed sheet according to claim 13, wherein the crosslinking agent is an epoxy-based crosslinking agent or an isocyanate-based crosslinking agent.

Citation Information

Patent Citations

  • Display unit drive system

    JP1977007277A

  • Inorganiccfiber reinforced gypsum composition

    JP1979054137A

  • Foam and laminate

    JP1997263651A

  • Polyester resin composition, stretched molded article and method for producing stretched molded article

    JP2004244457A

  • Polylactic acid resin foamed sheet for thermal forming and polylactic acid resin formed foam

    JP2004359910A